Association of left atrial pressure with late gadolinium enhancement extent in patient who underwent catheter ablation for atrial fibrillation - Seung-Young Roh (Nature Portfolio, 2020)
Abstract Atrial remodeling with fibrosis has been well-described in patients with atrial fibrillation (AF). We hypothesized that the left atrial (LA)-late gadolinium enhancement (LGE) extent on cardiac magnetic resonance (CMR) imaging is associated with LA pressure and can be a marker for suitable candidates for non-paroxysmal AF ablation. A total of 173 AF patients with an LA-LGE area on CMR imaging were enrolled. The clinical parameters, including invasively measured LA pressure, were compared between the patients with extensive LA-LGE (E-LGE, LGE extent ≥ 20%, n = 78) and those with small LA-LGE (S-LGE, LGE extent < 20%, n = 95). The E-LGE group had higher peak LA pressures than the S-LGE group (23 versus 19 mmHg, p < 0.001). The E-LGE group had more patients with non-paroxysmal AF (non-PAF) (51% vs. 34%), heart failure (9% vs. 0%), and higher NT pro-B-type natriuretic peptide (472 vs. 265 pg/ml) (all p < 0.05). LA pressure ≥ 21 mmHg was an independent predictor of E-LGE (OR = 2.218; p = 0.019). In the paroxysmal AF (PAF) subgroup, freedom from atrial arrhythmia after catheter ablation was not different (81% vs 86%, log-rank p = 0.529). However, in the non-PAF subgroup, it was significantly higher in the S-LGE group than in the E-LGE group (81% vs 55%, log-rank p = 0.014). Increased LA pressure was related to the LA-LGE extent. LA-LGE was a good predictor of outcome after catheter ablation, but only in patients with non-PAF.